Growth of Greater White‐Fronted Goose Goslings Relates to Population Dynamics at Multiple Scales. Issue 8 (3rd September 2021) - Fondell, Thomas F.; Meixell, Brandt W.; Flint, Paul L.
ABSTRACT: The abundance of greater white‐fronted geese ( Anser albifrons frontalis ) on the Arctic Coastal Plain (ACP) of northern Alaska, USA, has more than tripled since the late 1990s; however, recent rate of annual population growth has declined as population size increased, which may indicate white‐fronted geese on the ACP are approaching carrying capacity. We examined rates of gosling growth in greater white‐fronted geese at 3 sites on the ACP during 2012–2014 to assist with predictions of future population trends and assess evidence for density‐dependent constraints on recruitment. We marked goslings at hatch with individually coded webtags and conducted brood drives during early August to capture, measure, and weigh goslings. Annual estimates of gosling mass at 32 days old (range = 1, 190–1, 685) indicate that goslings had obtained >60% of asymptotic size. This rate of growth corresponds with that of other goose species and populations with access to high‐quality forage and no limitations on forage availability, and is consistent with the overall increase in abundance of white‐fronted geese at the ACP scale. Contrary to most previous investigations, age‐adjusted mass of goslings did not decline with hatch date. Goslings grew faster in coastal areas than at inland freshwater sites. Taken together, these findings suggest forage was not limiting gosling growth rates in either ecosystem, but forage was of greater quality in coastal areas where goose foraging habitat is expanding because of permafrost subsidence. Spatial patterns of gosling growth corresponded with local‐scale patterns of population density and population change; the areas with greatest rates of gosling growth were those with the greatest population density and rates of population increase. We found little evidence to suggest forage during brood rearing was limiting population increase of white‐fronted geese on the ACP. Factors responsible for the apparent slowing of ACP‐wide population growth are likely those that occur in stages of the annual cycle outside of the breeding grounds. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Gosling white‐fronted geese had high growth rates and our data did not suggest forage during brood rearing was limiting population increase of white‐fronted geese on the Arctic Coastal Plain of northern Alaska. Spatial patterns of variation in gosling growth corresponded with patterns of population growth and density.